PELATIHAN PEMBUATAN BRIKET UNTUK MASYARAKAT BELUM PRODUKTIF DI KEBON JERUK, JAKARTA BARAT - Chusniyah, Dina Asmaul; Pratiwi, Reno; Benyamin; Akbar, Rizki; Sugiarti, Lisa; Abidin, Muhammad Zainal (Universitas Trisakti, 2023)
One of the issues facing the planet is energy. Energy's significant role influences numerous local economic activities in society. To prepare for growing fuel prices, cheap, accessible alternative fuel is required. The strategy employed for this community service is socialization and training, and it is done offline (face-to-face) while still paying attention to the health program. This PkM task is broken down into multiple steps. Planning comes first, followed by gathering equipment and supplies, making briquette samples, and finally, implementing the strategy. The activity found that approximately 15 housewives participated in this PkM activity. Providing information about the energy sources needed in Indonesia and their use is part of this PkM's work program. The community service projects that have been completed are anticipated to have a beneficial impact on society and the environment, mainly on the locals of Gili Sampang Kebon Jeruk. The training participants were quite proactive during the activity, which can be proven from several questions to make alternative energy fuels good and maximum that the community can utilize. The PkM team and participants created a mutual agreement that synergizes with each other to develop alternative energy sources in the form of fuels that benefit the community.